Representasi Ideologi Gender di Korea Selatan dalam Drama Korea “Because This Is My First Life” - Eka Herlina (Pascasarjana ISBI Bandung, 2019)
In spite of its rapid modernization, South Korea is still having problems with gender issues in its socio-cultural life. The paper is aimed to reveal the reality of gender ideology in South Korea through a K-drama entitled “Because This Is My First Life”. It tells about the life of metropolis urban society. A drama or soap opera is the representation of reality in a life. The paper is a qualitative study applying discourse analysis to uncover the gender ideology in the story of the flm. The result showsthat the characters created in the story of the flm are submissive to the patriarchy values among the modernity of South Korea.Keywords : Representation, Gender ideology, Patriarchy, South Korea, K-drama